2022
DOI: 10.1021/acs.jpclett.2c02167
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Suppression of Majority Surface States in the Dry-Etched β-Ga2O3

Abstract: Surface treatment after dry etching is vital to enhance the surface quality of the material and thus improve device performance. In this Letter, we identified the majority surface states induced by the dry etching of β-Ga 2 O 3 and optimized surface treatments to suppress these electrically active defects with the improved performance of Schottky barrier diodes. Transient spectroscopies suggested that the majority traps (E C −0.75 eV) related to divacancies (V Ga −V O ) were enhanced in the concentration of 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…38 However, the RIE process causes plasma damage on the processed surfaces, resulting in interface traps that degrade device performances due to limited effective channel mobility 31 and a large hysteresis loop 28 in FinFETs and increased on-resistance in MOSSBDs. 35 To restore device performances, the plasma damage should be removed through wet treatments in acid or alkaline solutions, 39-42 annealing, 41,43 or selfreaction etching with gallium flux. 42 However, plasma-free anisotropic etching approaches have been explored to produce plasma-damage-free high-aspect-ratio structures.…”
mentioning
confidence: 99%
“…38 However, the RIE process causes plasma damage on the processed surfaces, resulting in interface traps that degrade device performances due to limited effective channel mobility 31 and a large hysteresis loop 28 in FinFETs and increased on-resistance in MOSSBDs. 35 To restore device performances, the plasma damage should be removed through wet treatments in acid or alkaline solutions, 39-42 annealing, 41,43 or selfreaction etching with gallium flux. 42 However, plasma-free anisotropic etching approaches have been explored to produce plasma-damage-free high-aspect-ratio structures.…”
mentioning
confidence: 99%
“…Figure 2(a) shows the influence of RF power on the etching rate. Since RF power determines the power of the material surface bombarded by plasma, [17][18][19][20][21][22][23][24] the etching rate increases from 72 to 86 nm min −1 as the RF power increases from 100 to 300 W. As shown in Fig. 2(b), the θ decreases as the RF power increasing from 100 to 250 W. In the process of ICP etching, due to the joint action of physical and chemical etching, a beveled sidewall will naturally be formed.…”
Section: Resultsmentioning
confidence: 96%
“…The Bardeen model suggests that electron transfer from the semiconductor to the metal is mediated by interface states on the contact surface, assuming a continuous distribution of surface states defined by a neutral energy level Φ 0 , with the Fermi level position determined by the location of the surface states within the bandgap, which is the Fermi level pinning effect [115]. Therefore, the surface states of β-Ga 2 O 3 also significantly affect device performance; experiments have found that treatments such as oxygen plasma and annealing, as well as chemical solution cleaning, can effectively reduce the density of surface states on β-Ga 2 O 3 , enhancing device performance, while etching and plasma bombardment may increase surface state density, leading to poorer device performance [116][117][118][119][120][121].…”
Section: Schottky Contactmentioning
confidence: 99%